2013
DOI: 10.1038/eye.2013.119
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic ability of retinal nerve fiber layer maps to detect localized retinal nerve fiber layer defects

Abstract: Purpose To evaluate and compare the diagnostic ability of spectral domain optical coherence tomography (SD-OCT) for detecting localized retinal nerve fiber layer (RNFL) defects in topographic RNFL maps and circumpapillary RNFL (cpRNFL) thickness measurements. Methods Sixty-four eyes with localized RNFL defects in red-free RNFL photographs and 72 healthy eyes were included. All participants were imaged with SD-OCT. The area and angular width of the localized RNFL defects were measured with ImageJ software on RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Several previous studies have reported similar results, finding that the RNFL deviation map significantly improves the diagnostic sensitivity for localized RNFL defects or glaucoma detection compared with conventional circumpapillary RNFL measurement [4, 14, 16]. A broader imaging area of SD-OCT provides a greater chance to find signs of RNFL damage.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Several previous studies have reported similar results, finding that the RNFL deviation map significantly improves the diagnostic sensitivity for localized RNFL defects or glaucoma detection compared with conventional circumpapillary RNFL measurement [4, 14, 16]. A broader imaging area of SD-OCT provides a greater chance to find signs of RNFL damage.…”
Section: Discussionsupporting
confidence: 52%
“…The best circumpapillary RNFL parameter was inferior RNFL thickness (0.914) in the localized RNFL defect group, and average RNFL thickness (0.986) in the diffuse RNFL defect group. Table 4 presents a number of previous studies on the diagnostic ability of circumpapillary RNFL thickness in glaucoma patients [4, 1422]. In the studies of localized RNFL defects, sectoral RNFL measurements (clock-hour or inferior quadrant) were the most useful parameters [1417].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that localized and diffuse defects in glaucoma predominantly affect the inferior quadrant. 16,44 In moderate to advanced glaucoma, localized RNFL defects constitute 4.2% of the defects, whereas 94.5% demonstrate diffuse defects. In addition to that, diffuse RNFL defects are located closer to the optic disc than localized RNFL defects.…”
Section: Discussionmentioning
confidence: 99%
“…30 After comparing our study results with those of previous studies performed with the same Topcon OCT device but in adults, we found similar mRNFL values, although GCL-IPL values were thicker in paediatric patients. In their investigations in adults, Shin et al 31 and Kim et al 32 found, respectively, the following values: superior mRNFL, 33.9 AE 5.0 μm and 34.81 AE 3.93 μm; inferior mRNFL, 37.3 AE 4.7 μm and 37.89 AE 4.38 μm; total mRNFL, 35.5 AE 4.4 μm and 36.32 AE 3.75 μm; superior GCL-IPL, 71.4 AE 6.0 μm and 71.57 AE 5.37 μm; inferior GCL-IPL, 70.1 AE 5.9 μm and 69.49 AE 5.15 μm; and total GCL-IPL, 70.8 AE 5.1 μm and 70.49 AE 5.04 μm. As GCL-IPL tends to be thicker in children than in adults, the main difference between adult and paediatric GCL-IPL categories is an overdiagnosis of normality when using the adult database.…”
Section: Gcl-ipl Totalmentioning
confidence: 96%